Body representation in dreams of congenital and early-life amputees - Diers, Martin; Schredl, Michael; Flor, Herta; Bekrater-Bodmann, Robin (Scientific reports, 2025)
Phantom limb pain (PLP) is a common consequence of the amputation of a limb. Individuals with congenital limb absence (here: congenital amputees), however, seem to rarely experience PLP. Previous results suggest that the experience of PLP in the waking state affects the recalled body appearance in dreams of individuals with acquired limb amputation, with PLP being associated with the recall of an impaired rather than an intact body. However, it remains unclear how congenital amputees - who never experienced an intact body and rarely PLP - recall their body appearance in dreams. In the present cross-sectional study, we assessed body-related dream content in a sample of adult congenital amputees and compared their reports with those from adult persons with an acquired limb amputation early in life. We found that congenital amputees reported the least frequent dreams with an intact body, and after birth, the age at amputation positively predicted the recall of an intact body in dreams. The effects were not explained by time since amputation and the presence or absence of PLP. This suggests that life experiences of an intact body find expression in self-related dream content.